Impact of International Rating Agencies in Iberian Private Companies - Vasco Soares; Sónia Carvalho; Mafalda Mendes-Ribeiro (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
The impact of international rating agencies addressing political risk in Iberian private companies is a factor of the outmost importance for corporate decisions concerning capital structure and leverage, although not yet properly addressed in recent research. The financial crisis in the new millennium together with the notation of Portugal by international rating agencies raised issues about political risk impact in the financing of companies and how changes in political risk could affect the perception of the of managers about the capital structure of the companies. The time frame has been selected for incorporating recent and large financial crisis with an impact on the country’s political risk change, from 2003 to 2015. Starting with correlations between Leverage and variables Return on Assets, Return on Equity, Dimension, Tangibility, Sales Variation, Political Risk, and Critical Political Risk, the results were determined through an empirical investigation with a new econometric model. On the Credit Rating Agencies’ notations, Critical Political Risk is a dummy variable. We analyse the problem of how this notation affects domestic Political Risk and affects enterprises’ capital structure, taking into account the influence of this international notation. Our premise was supported by evidence: when political risk rises, leverage began to decrease. Further study interests include determining how CPR affects each firm, calculating risk per company, and analysing the impact of Rating Notation on financing decisions in private companies from the Iberian Market.